A critical analysis of the scope of the foreign services reportable arrangement provision of the Tax Administration Act of South Africa - Oosthuizen, Marlene (Stellenbosch : Stellenbosch University, 2019)
Thesis (MCom)--Stellenbosch University, 2019.